The Relationship between Diastolic Blood Pressure and the Event of the First Ischemic Stroke in Hypertension Patients - Surbakti, Epa Danisa; Rambe, Aldy S.; Pujiastuti, R.A. Dwi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Stroke has been the second leading cause of death and the third cause of disability worldwide. A record of hypertension and an increase in diastolic blood pressure (DBP) after the first stroke were associated with an increased risk of a second stroke. DBP has historically been considered as the leading cause of cardiac arrest in adults with hypertension. In the previous studies, it was found a relationship between DBP with stroke and functional outcomes. AIM: This research was carried out to determine the relationship between DBP and the event of ischemic stroke for the 1st time in hypertension patients. METHODS: This research is a case–control that was selected using a consecutive sampling technique, where 47 hypertensive patients with ischemic stroke as the case group were matched with 47 hypertensive patients without stroke as the control group. The research was conducted at H. Adam Malik Hospital, Medan and a network hospital. RESULTS: In this research, most samples in the case and control groups were men with 30 subjects (63.8%) with a mean age value of 58.11 ± 10.85 years. At TDD ≥90 mmHg, 34 subjects (72.3%) had ischemic stroke and 21 subjects (44.7%) did not. At TDD <90 mmHg, the percentage of ischemic stroke was 13 subjects (27.7%) and 26 subjects (55.3%) were non-ischemic stroke with p = 0.006, OR = 3.02. CONCLUSION: There is a significantly close relationship between diastolic blood pressure and the event of ischemic stroke.